Design of interactive multimedia courseware in data structures & Algorithms - I - Lo, Cai Ling (2014)
As the advancement of technology, our lives have been enriched with multimedia and interactive devices. In order to have a two-way interaction with the user, a website must be simplified and efficient for users to get hold of the information as well as being interesting too. The E-learning website will help students to engage in activities, interaction and makes them understand the topic well. The report will cover the methodology used, research finding and lastly conclusion.